2018
DOI: 10.4155/tde-2017-0123
|View full text |Cite
|
Sign up to set email alerts
|

Topical Oral Wound Healing Potential of Anthocyanin complex: Animal and Clinical Studies

Abstract: At 10% w/w, AC promoted wound closure and possessed a potential in healing stimulation of acute oral wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…ANT-demonstrated benefits include protection against diabetes [6, 7], impressive reduction of blood pressure, enhancement of vision [8, 9], and strong anti-inflammatory effects [10, 11]. These phenolic compounds also facilitate dermal and oral wound healing [11, 12]. Fibroblast proliferation influences the formation of granulation tissue, collagen synthesis, and wound contraction.…”
Section: Introductionmentioning
confidence: 99%
“…ANT-demonstrated benefits include protection against diabetes [6, 7], impressive reduction of blood pressure, enhancement of vision [8, 9], and strong anti-inflammatory effects [10, 11]. These phenolic compounds also facilitate dermal and oral wound healing [11, 12]. Fibroblast proliferation influences the formation of granulation tissue, collagen synthesis, and wound contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Each FPM solution contained in a 5 mL syringe and weighing approximately 5 g and was loaded into the donor chamber, and the receptor chamber was filled with 1% bovine serum albumin solution (Sigma-Aldrich, USA) in phosphate buffer at pH 7.4 to maintain a sink condition [ 16 ]. This was stirred at 600 rpm at 37 ± 2 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In the animal model, a reduction in the erythema and the sizes of oral wounds was observed compared to placebo gel. In the clinical trial, wound closure enhancement was observed on day 3 of anthocyanin gel application [216].…”
Section: Medicinal Products Developed With Ansmentioning
confidence: 99%